KARAKTERISTIK KLINIKOPATOLOGI KANKER LAMBUNG - Erawan, I Putu Putra; Ekawati, Ni Putu; Sumadi, I Wayan Juli; Saputra, Herman (E-Jurnal Medika Udayana, 2023)
ABSTRACT Gastric cancer is a malignant neoplasm of the stomach and can invade and spread to other organs. Cases of gastric cancer are still common throughout the world and tend to be potentially deadly, especially among older men. Based on data obtained through GLOBOCAN in 2018, gastric cancer is a neoplasm with the 5th most common occurrence in the world and the 3rd deadliest cancer in the world, with an estimated 783,000 deaths in 2018. The purpose of this study is to determine the profile of gastric cancer patients at Sanglah Hospital from 2010 to 2020. This research is classified as a descriptive study using a cross-sectional method. The sample used was selected based on inclusion and exclusion criteria. The subjects of the study were 21 gastric cancer patients at Sanglah Hospital in 2010-2020. Data retrieval from medical records was then analyzed with SPSS version 22 software. The results of the study showed that the profile of gastric cancer patients at Sanglah Hospital in 2010-2020 varied greatly, with the most occurring in the age group above 50 years. By gender, the majority of cases are women. For clinical diagnosis, the most frequently found is dyspepsia. Keywords : Characteristics, Gastric Cancer, Sanglah General Hospital